Poświadczenie podpisu w postępowaniu administracyjnym - Artymionek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents changes to administrative procedure effected under the Act of 23 October 2009, amending laws with regard to authentication of documents. The author analyzes the problems concerning authenticity of signatures, certification of signatures and official certification of a signature by a party exercising power of attorney, in light of Article 33 3 of the Code of Administrative Procedure. The author points out errors made by public agencies and possible procedural consequences arising from failure to comply with the request of the agency. He also answers the questions: Does the new regulation improve the procedural situation of a party to the proceedings? Who is authorized to certify signatures? Is the certification of a signature the same as the official certification of a signature? And finally, how, in case of doubt, should we assess the legitimacy of a public administration agency requiring that a power of attorney bear an officially certified signature of a party?The basic conclusion of the article is that the official certification of a signature is within its scope contained in the certification of a signature, whereas beyond its legal scope, the provisions of the Law on Notaries should be applicable; and also that the devolvement of powers to a public administration agency under Article 33 3 3 of the Code of Administrative Procedure will not improve the procedural situation, but may in some cases exacerbate it.
Keywords: poświadczenie podpisu; autentyczność podpisów; urzędowe poświadczenie podpisów; aktywny udział strony w postępowaniu administracyjnym; uprawnienia organu administracji publicznej